Impact of the North Sea–Caspian pattern on meteorological drought and vegetation response over diverging environmental systems in western Eurasia. Issue 5 (24th June 2022) - He, Qing; Xu, Bolin; Dieppois, Bastien; Yetemen, Omer; Sen, Omer Lutfi; Klaus, Julian; Schoppach, Rémy; Çağlar, Ferat; Fan, Ping Yu; Chen, Liang; Danaila, Luminita; Massei, Nicolas; et al.
Abstract: Emerging drought stress on vegetation over western Eurasia is linked to varying teleconnection patterns. The North Sea–Caspian Pattern (NCP) is a relatively less studied Eurasian teleconnection pattern, which has a role on drought conditions and the consequence of changing conditions on vegetation. Between 1981 and 2015, we found that the Standardized Precipitation Index (SPI) and the Normalized Difference Vegetation Index (NDVI) have different trend patterns over various parts of western Eurasia. Specifically, the vegetation greenness is linked with wetter conditions over Scandinavia, and vegetation cover decreases over a drying central Asia. However, western Russia and Franceare paradoxically becoming greener under drier conditions. Using the Budyko framework, such paradoxical patterns are found in energy‐limited environmental systems, where vegetation growth is primarily promoted by warmer temperatures. While most studies focused on the impacts of the North Atlantic Oscillation (NAO), we test whether the NCP explains better the variability of meteorological drought and vegetation response over western Eurasia. We hypothesised that the positive phases of the NCP are correlated to high pressure anomalies over the North Sea, which can be associated with weakening onshore moisture advection, leading to warmer and dryness conditions. These conditions are driving vegetation greening, as western Eurasia is mainly energy limited. However, we show that as the climate is warming along with the teleconnection impacts, the future ecosystem over western Eurasia will be transferred from energy‐limited to water‐limited systems. This suggests that the observed vegetation greening over past three decades is unlikely to sustain in the future. Significance statement: Meteorological droughts affect vegetation cover differently across western Eurasia depending on water and energy supply. Droughts hinder vegetation development in water‐limited areas, but promote vegetation growth in energy‐limited areas due to rising temperatures. The teleconnections that influence precipitation and temperature patterns are linked to these patterns of vegetation responses. The North Sea‐Caspian Pattern (NCP) explains more variance between meteorological drought and vegetation response over western Eurasia than the North Atlantic Oscillation (NAO). The observed vegetation greening over the last three decades is unlikely to persist, given the effects of rising temperatures and NCP changes.